The Effect o f Credibility i n Social Networking Site : A Case Study on Palestinian Journalistic Discourse - Yousef A. Y. Almadhoun; Nur Kareelawati Binti Abd. Karim; Osama Kanaker (Genius Journals, 2021)
This studyseeks to providea new perspective on credibility and the effect of reliable source in the newsworthy, especially with the increased rates and the criticalrole of SNSs in providing newsworthy. Further, the study attempts to invistagte the dimessions of credibility among journalists, especially in the midst of  critical situations and serious circumestances happened across the world which represent wet materials for such news websites to flowing news stories, editorials and texts. The results of this research contribute to identifying journalists' perceptions of the credibility of social networking sites as a source of information in their work in order to provide an optimal description of the findings. Finally, the results of this research contribute to the literature realatedto media in general and wide understanding tothe social media practices in palestine in particular. In addition,it triesto reveals suggestions which can overcome the gapofcredibility between social networking sites and/or social media disseminated in Palestine.
Keywords: Social Media; Traditional Journalism; Facebook; Twitter